Lysine in Combination With Estradiol Promote Dissemination of Estrogen Receptor Positive Breast Cancer via Upregulation of U2AF1 and RPN2 Proteins - Vazquez Rodriguez, Gabriela; Abrahamsson, Annelie; Turkina, Maria V.; Dabrosin, Charlotta (Frontiers in Oncology, 2020)
The majority of estrogen receptor positive (ER+) breast cancer (BC) maintain the ER at metastatic sites. Despite anti-estrogen therapy, almost 30% of ER+ BC patients relapse. Thus, new therapeutic targets for ER+ BC are needed. Amino acids (AAs) may affect the metastatic capacity by affecting inflammatory cells. Essential AAs (EAAs) cannot be produced by human cells and might therefore be targetable as therapeutics. Here we sampled extracellular EAAs in vivo by microdialysis in human BC. Mass spectrometry-based proteomics was used to identify proteins affected after EAA and estradiol (E2) exposure to BC cells. Proteins relevant for patient survival were identified, knocked down in BC cells, and metastatic capability was determined in vivo in the transgenic zebrafish model. We found that lysine was the most utilized EAA in human ER+BC in vivo. In zebrafish, lysine in presence of E2 increased neutrophil-dependent dissemination of ER+ BC cells via upregulation of U2AF1 and RPN2 proteins, which both correlated with poor prognosis of ER+ BC patients in clinical databases. Knockdown of U2AF1 and RPN2 decreased the expression of several cell-adhesion molecules resulting in diminished dissemination. Dietary lysine or its related metabolic pathways may be useful therapeutic targets in ER+ BC.